DESIGN AND DEVELOPMENT OF A SYSTEM BASED APPLICATION FOR READING AND LEARNING AYURVEDA SUTRAS - B S, JANANYA; PAVANA N; AYUSH DRAVID SM; DR. G MANJULA; DR. ARPANA P (International Journal of Multidisciplinary Research and Studies, 2022)
The main objective of this application is to provide the user with a better understanding and learning of the Ayurvedic sutras. Because most Ayurvedic sutras are based in Sanskrit, it is difficult for everyone to learn and understand the same. So, with this application users can realize the sutras and implement them. The basic idea of this application is to provide the user with audio of the sutra and the context of that particular sutra.